Sistem Kontrol pH dan Nutrisi Otomatis pada Tanaman Hidroponik Bayam Berbasis fuzzy logic - Kukuh Setyohadi; Ibrahim Ibrahim; Reni Rahmadewi (Peneliti.net, 2021)
The hydroponic method is one way of cultivating plants without using soil. In this method the plants are hung in a pipe gap and drained with water, in the process of planting it takes accuracy in treating the condition of the water used to circulate plants, because the health of plants depends on water conditions. Things that must be considered in hydroponic planting include the pH of water and nutrition. This study aims to regulate pH and nutrient conditions in hydroponic plants automatically by applying a fuzzy logic-based control system so that pH and nutrient conditions are always well maintained. The sensors used in this study are pH sensors, TDS sensors (Total Dissolve Solid), and ultrasonic sensors. The results of the research that have been done show that the system design can work with an average percentage of error in the pH control of 0.039% and in the nutrition control of 0.017% with a system accuracy of 99.94%.